2015
DOI: 10.1177/0301006615596868
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Saccadic Eye Movement in Hemiparkinsonian MPTP-Treated Monkeys

Abstract: The saccadic eye movements declining given the development of Parkinson's disease (PD) still deserves thorough analysis. Recent studies confirmed that PD patients show poor saccadic control in visuomotor tasks. The purpose of this study was to investigate the dynamics of saccades parameters at the development of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of PD. The gradual decline of saccadic control was studied in two monkeys that executed the visuomotor task with low doses of MPTP being inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Stimulating the frontal eye field and supplementary eye field with transcranial magnetic stimulation (TMS) increased the incidence of MSS ( van Donkelaar et al, 2009 ). Loss of dopaminergic neurons in the basal ganglia increased the incidence of MSS, as observed in PD patients ( Kimmig et al, 2002 ; Blekher et al, 2009 ) and PD monkeys ( Tereshchenko et al, 2015 ). Lesions in the cerebellum caused an increase in MSS incidence in human and non-human primates ( Avanzini et al, 1979 ).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Stimulating the frontal eye field and supplementary eye field with transcranial magnetic stimulation (TMS) increased the incidence of MSS ( van Donkelaar et al, 2009 ). Loss of dopaminergic neurons in the basal ganglia increased the incidence of MSS, as observed in PD patients ( Kimmig et al, 2002 ; Blekher et al, 2009 ) and PD monkeys ( Tereshchenko et al, 2015 ). Lesions in the cerebellum caused an increase in MSS incidence in human and non-human primates ( Avanzini et al, 1979 ).…”
Section: Discussionmentioning
confidence: 75%
“…While the reported incidences of MSS are consistent for memory guided saccades among previous studies, the results are inconsistent for reactive saccades. Some studies reported that, compared with elderly healthy subjects, the incidences of MSS are significantly higher in both PD patients ( Jones and DeJong, 1971 ; Corin et al, 1972 ; White et al, 1983 ) and PD monkeys ( Brooks et al, 1986 ; Tereshchenko et al, 2015 ), but others reported no significant difference ( Crawford et al, 1989 ; Lueck et al, 1990 , 1992 ; Van Gisbergen et al, 1992 ; Kimmig et al, 2002 ; Blekher et al, 2009 ). We think that a possible reason for such inconsistency might be the different definitions of MSS.…”
Section: Introductionmentioning
confidence: 99%
“…Supportively, previous studies have found that suppressing the activity of the frontal eye field (FEF) and supplementary eye field by transcranial magnetic stimulation (TMS) increased the incidence of MSS (van Donkelaar et al, 2009). Moreover, damage of dopaminergic neurons in the basal ganglia increased the incidence of MSS, as observed in PD patients (Kimmig et al, 2002;Blekher et al, 2009) and in PD monkeys (Tereshchenko et al, 2015).…”
Section: The Higher Oculomotor Structures In Cortical and Subcortical...mentioning
confidence: 82%